Design of Two Channel Infusion Pump Analyzer Using Photo Diode Detector - Syaifudin , Syaifudin; Mak’ruf, Muhammad Ridha; Luthfiyah, Sari; Sumber, Sumber (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2021)
In the medical world, patient safety is a top priority. The large number of workloads and the frequency of using the devices in the long run will affect the accuracy and accuracy of the tool. If the flow rate and volume of the syringe pump or infusion pump given to the patient are not controlled (overdose or the fluid flow rate is too high) it can cause hypertension, heart failure or pulmonary edema. Therefore, it is necessary to have a calibration, which is an application activity to determine the correctness of the designation of the measuring instrument or measuring material. The purpose of this research is to make a two channel infusion device analyzer using a photodiode sensor. The contribution of this research is that the system can display three calibration results in one measurement at the same setting and can calibrate 2 tools simultaneously. The design of the module is in the form of an infrared photodiode sensor for reading the flowrate value. This study uses an infrared photodiode sensor for channels 1 and 2 installed in the chamber. This study uses a flow rate formula that is applied to the water level system to obtain 3 calibration results. Infrared photodiode sensor will detect the presence of water flowing in the chamber from an infusion or syringe pump. Then the sensor output will be processed by STM32 and 3 calibration results will be displayed on the 20x4 LCD. This tool has an average error value on channel 1 of 3.50% and on channel 2 of 3.39%. It can be concluded that the whole system can work well, the placement and distance between the infrared photodiodes also affects the sensor readings